A prospective randomised study of "covered" versus "uncovered" diamond stents for the management of distal malignant biliary obstruction. (13th April 2004) - Isayama, H; Komatsu, Y; Tsujino, T; Sasahira, N; Hirano, K; Toda, N; Nakai, Y; Yamamoto, N; Tada, M; Yoshida, H; Shiratori, Y; Kawabe, T; et al.
Abstract : Background and aim: Covered self-expandable metal stents (EMS) were recently developed to overcome tumour ingrowth in conventional EMS. However, supporting evidence for the efficacy of covered EMS is lacking. Patients and methods: We enrolled 112 patients with unresectable distal biliary malignancies. They were randomly assigned to polyurethane covered (n = 57) or original diamond stent (n = 55). Results: Stent occlusion occurred in eight patients (14%) after a mean of 304 days in the covered group, and in 21 patients (38%) after a mean of 166 days in the uncovered group. The incidence of covered EMS occlusion was significantly lower than that of uncovered EMS (p = 0.0032). The cumulative stent patency of covered stents was significantly higher than that of uncovered stents (p = 0.0066). No tumour ingrowth occurred in the covered group while it was observed in 15 patients in the uncovered group. In subgroup analysis, the cumulative patency of the covered EMS was significantly higher in pancreatic cancer (p = 0.0363) and metastatic lymph nodes (p = 0.0354). There was no significant difference in survival between the two groups. Acute cholecystitis was observed in two of the covered group and in none of the uncovered group. Mild pancreatitis occurred in five of the covered group and in one of the uncovered group. Conclusions: Covered diamond stents successfully prevented tumour ingrowth and were significantly superior to uncovered stents for the treatment of patients with distal malignant biliary obstruction. However, careful attention must be paid to complications specific to covered self-expandable metal stents, such as acute cholecystitis and pancreatitis.